Extraction and purification of anthocyanin from Antidesma bunius for visible photocatalysis - Nonog, Ma. Eden Dorothy Q.; Mercado, Candy C. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
Anthocyanin is group of pigments that have a potential to be used for photocatalysis and other visible light adsorption. Anthocyanin can be extracted from Antidesma bunius using 70% acidified ethanol for 2 hr. Purification can be done using 1:1 ration of the chloroform and the crude extract. The extraction time has the most significant effect on the extraction followed by the acid and the extracting solvent concentration. The adsorption mechanism of the anthocyanin onto TIO₂ substrate is found to fit the Langmuir Isotherm model which implies that the mechanism is monolayer. Anthocyanin is more stable in low pH compared to higher pHbut degrades 10% more in low pH when exposed to sunlight. The redox behaviour is found to be similar to that of peonidin-3-O-glucoside with two anodic peaks occuring at 377 mV and 990 mV. Peonidin-3-O-glucoside is one of the major pigments in sweet cherry fruit trees. This confirms that the extracted solution contains anthocyanin pigments. The facile extraction, stability in low pH, and monolayer adsorption makes anthocyanin from Antidesma bunius a viable source of natural colorants and antioxidants that can be used for photocatalysis or any visible light absorber applications.
Thesis (Bachelor of Science in Materials Engineering)--University of the Philippines Diliman
Keywords: Anthocyanins